Can in-store interventions reduce the socioeconomic gap in fruit and vegetable purchases in grocery stores? A descriptive study of volume sales from 2012 to 2020 in Norway's largest grocery store chain. (1st September 2022) - Slapø, Helena; Bugge, Annechen Bahr; Sandaker, Ingunn; Lekhal, Samira
Abstract: Fruits and vegetable (FVs) consumption is an essential determinant of health, and intake is strongly patterned by socioeconomic status (SES). Inside grocery store interventions have increasingly been explored to promote healthier diets, especially for people with lower SES. This study describes how the supermarket chain Kiwi used a combination of in-store interventions to increase annual sales of FVs between 2012 and 2020. In particular, this study examined how sales developed in counties with different demographic characteristics (e.g., education, income, overweight and obesity, and self-reported FVs consumption level) in order to evaluate whether the effect differs between different populations. The primary outcome measurement was annual volume sales, adjusted for new stores opening and closing during the study period, also called like-for-like sales. The study has used a descriptive study design. The chain used interventions such as better placement, promoting healthy foods, giving out discounts, and placing "on the go" FVs and cups with portioned FVs at the cash registry. Results show that like-for-like volume sales of FVs grew by 34.1% during the study period. The increase was especially strong for vegetables, which increased by 41.8%, compared to fruits and berries, which increased by 25%. Sales increased for all eleven counties in Norway. Using the Spearman correlation, a moderately positive association was found between the number of overweight or obese people in counties and the development in FVs sales. To conclude, in-store interventions positively impacted FVs sales. More research in an experimental context is needed to determine if interventions may reduce the socioeconomic gap in FVs consumption.